Investigation of the Hydrodynamics of Fixed Bed Reactor: Co-current Upflow - Abdul Manan, Nurhafizati (Universiti Teknologi Petronas, 2005)
The main objective ofthis project is to investigate the hydrodynamic characteristics of co-current upflow of gas and liquid in a fixed bed reactor. This is an experimental based project utilizing the packed bed reactor for residence time distribution (RTD) studies. In this project, the RTD of a bench-scale multiphase was studied using air as a gaseous phase and water as a liquid phase. The ranges of air and water velocities are kept at such levels as to simulate the hydrogen/oil ratios of typical bench-scale hydroprocessing units. The experiments are conductedin upflowmode of operationin the reactor, with increasing gas/liquid ratio. The effects of gas and liquid velocities on different hydrodynamic parameters such as pressure drop and operating liquid holdup are investigated. Three moments analysis, which are mean residence time, variance, and skewness, are evaluated in order to characterize the RTD. Other parameters such as bed Peclet number of liquid and stagnant zone volume were also investigated with variation of gas and liquid velocities as to measure the efficiency of the reactor. The discrepancies in experimental results suggested that there are conditions to be altered in order to eliminate the inconsistency.